The image of a horseman in the sunlight: Heraldic cases of Bashkortostan and Tuva - Rakhimov, Ramil N.; Aznabaev, Bulat A.; Frolova, Irina V. (The New Research of Tuva, 2022)
In the 1920s–1930s, a process of constitutional development and creation of symbols of statehood took place in the national republics of the RSFSR and the Tuvan People’s Republic. In 1925, the coat of arms was adopted in the Autonomous Bashkir Soviet Socialist Republic, and it was based on the image of a horseman with a banner in the rays of the sun. The coat of arms was not approved by the federal center.In the 1930s, the process of “Sovietization” of the autonomies’ coats of arms led to the fact that all of them received the coat of arms of the RSFSR with the name of a particular republic. This phenomenon was associated with the failure of the policy of “korenizatsiya” (“indigenization”) which was pursued by the CPSU(b) in the USSR in 1923–1928. Aimed at creating a Soviet national elite, it led to the emergence of nationalism in the regions. The throwback to conservative positions forced the party leadership to move towards the unification of heraldic practice. In the Tuvan People’s Republic, the “leftist experiment” led to crisis phenomena which resulted in the retreat from the radical policy. The change of course led to the replacement of the “Soviet” version of the coat of arms with the “national” one that had the image of a horseman in the sun. In the coat of arms of 1935, the ancient Turkic cultural tradition was integrated with the Buddhist one through the sign of the mandala.In 1992–1993, the republics of Tuva and Bashkortostan — the subjects of the Russian Federation — adopted new coats of arms which are based on the image of a horseman in the rays of the sun. Tuva used the basis of the coat of arms of 1935, and Bashkortostan placed the monument to the national hero Salavat Yulaev in the sunshine on the coat of arms. The image of a horseman in the sun goes back to antiquity. It personifies the archetype of the nomad and harmony with nature. In the Turkic and Mongolian epic literature, the horse, in some cases, serves the function of the sun. The phenomenon of the heraldic tradition of Bashkortostan and Tuva lies in the fact that the ancient image as the basis of national identity in symbolic practice turned out to be more significant than images associated with religious or political identity.
Keywords: heraldry; national policy; USSR; history of Bashkortostan; Bashkortostan; history of Tuva; Tuva; horseman; coat of arms